Discovering banner blindness for different banner formats: An eye-tracking study - Nevzat Bilge İspir; Deniz Kılıç; Günay Motif Atar (Connectist Istanbul University Journal of Communication Sciences)
Banner blindness is ignoring the ads on internet websites either consciously or unconsciously, and it has been recently used as one of the new terms in the digital world. Advertisers struggle to overcome this blindness and get the audience to notice banners. Moreover, they work on creative advertisement ideas. As banner blindness increases, brands have to be more attentive and careful about where and how to use their banners. Therefore, advertisements must primarily be remarkable. In this study, measurements for banner blindness and attention variables were made by an eye-tracking device. In the 4x2 factorial experimental study, a news website was designed, and banners were created and placed on the website. 160 students took part in the experiment in an isolated room individually. According to the results, left-side banners and top-side banners got more fixation. The participants fixated at least once on horizontal banners more than vertical banners. The free surfing group found online ads more informative and believable than the focused group. If users focus on the website content, they cannot remember ad names and do not look at the banners. Therefore, the free surfing group remembered more ads than the focusing group. Banner type (visual or text-based) was not significantly effective on fixation.